Odpowiedzi

Najlepsza Odpowiedź!
2010-02-10T22:57:02+01:00
A) 11 - (5¾ + 2⅕) =11-(5 15/20+2 4/20)=11-7 19/20=3 1/20
b) 4 2/3 - ¾ + 1⅕ = 4 40/60- 45/60+1 12/60=4 7/60
c) 2,3/7 x (1⅓ + 2,1/6 )=2 3/7×(1 3/6+2 1/6)=2 3/7×3 4/6=14/7×22/6=22/3=7 1/3
d) 9,1/5 : (14 : 7/23) =9,1/5 :46=46/5 ×1/46=⅕
e) 6 : 9/10 + 3/5 : 4/5 =6×10/9+3/5×5/4=20/3+3/4=80/12+9/12=89/12=7 5/12
f) (5¾ + 4) x ⅓ =9¾×½=39/8=4 7/8
g) (7 : 2⅓ + 8½) : ½ =(7×2/5 + 8½) : ½=(28/10+8 5/10)×2=11 3/10×2=226/10=22,6
2010-02-10T23:03:09+01:00
A)
11 - (5¾ + 2.1/5) = 11-(5 15/20+2 4/20)=11-7 19/20=3 1/20
b)
4,2/3 - ¾ + 1,1/5 =4 40/60-45/60+1 12/60=5 7/60
c)
2,3/7 x (1⅓ + 2,1/6 =2 3/7×(1 2/6+2 1/6)=2 3/7×3 3/6=
=17/7×21/6=8,5
d)
9,1/5 : (14 : 7/23) =9 1/5:(14/1×23/7)=9 1/5:46=46/5×1/46=1/5
e)
6 : 9/10 + 3/5 : 4/5 =6/1×10/9+3/5×5/4=20/3+3/4=6 2/3+3/4=
=6 8/12+9/12=16 5/12
f)
(5¾ + 4) x ⅓ =9 3/4×1/3=39/4×1/3=13/4=3 1/4
g)
(7 : 2⅓ + 8½) : ½ = (7:7/3+8 1/2):1/2=(7/1×3/7+8 1/2):1/2=
=(3+8 1/2):1/2=11 1/2:1/2=23/2×2/1=23
2010-02-10T23:18:17+01:00
A) 11 - (5¾ + 2.1/5) = 11 - ( 23/4 + 11/5) = 11 - (115/20 + 44/20) =
= 11 - 159/20 = 11 - 7,95 = 3,05
b) 4,2/3 - ¾ + 1,1/5 = 14/3 - 3/4 + 6/5 = 280/60 - 90/60 + 72/60= 262/60=
= 4 i 22/60 = 4 i 11/30
c) 2,3/7 x (1⅓ + 2,1/6 =17/7 *(4/3 + 13/6) = 17/7 *(8/6 + 13/6) = 17/7*21/6=
= 17/2 = 8,5
d) 9,1/5 : (14 : 7/23) = 46/5 :(14 *23/7) = 46/5 :46 = 46/5*1/46= 1/5
e) 6 : 9/10 + 3/5 : 4/5 = 6 : 9/10 + 3/5 *10/9 = 6*10/9 + 2/3 = 20/3 + 2/3 = =22/3 = 7 i 1/3
f) (5¾ + 4) x ⅓ =( 9¾) *1/3 = 39/4*1/3 = 13/4 = 3 i 1/4
g) (7 : 2⅓ + 8½) : ½ = ( 7 *3/7 +8½ ) *2= (3 + 8½)*2 = 11½ *2 = 23